Intake of macro- and micronutrients in Danish vegans - Kristensen, Nadja B. (Nutr J, 2015)
BACKGROUND: Since information about macro- and micronutrient intake among vegans is limited we aimed to determine and evaluate their dietary and supplementary intake. METHODS: Seventy 18–61 years old Danish vegans completed a four-day weighed food record from which their daily intake of macro- and micronutrients was assessed and subsequently compared to an age-range-matched group of 1 257 omnivorous individuals from the general Danish population. Moreover, the vegan dietary and supplementary intake was compared to the 2012 Nordic Nutrition Recommendations (NNR). RESULTS: Dietary intake differed significantly between vegans and the general Danish population in all measured macro- and micronutrients (p < 0.05), except for energy intake among women and intake of carbohydrates among men. For vegans the intake of macro- and micronutrients (including supplements) did not reach the NNR for protein, vitamin D, iodine and selenium. Among vegan women vitamin A intake also failed to reach the recommendations. With reference to the NNR, the dietary content of added sugar, sodium and fatty acids, including the ratio of PUFA to SFA, was more favorable among vegans. CONCLUSIONS: At the macronutrient level, the diet of Danish vegans is in better accordance with the NNR than the diet of the general Danish population. At the micronutrient level, considering both diet and supplements, the vegan diet falls short in certain nutrients, suggesting a need for greater attention toward ensuring recommended daily intake of specific vitamins and minerals. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12937-015-0103-3) contains supplementary material, which is available to authorized users.